FLUCTUATIONS OF LITHUANIAN ECONOMY: IDENTIFICATION RULES AND FEATURES - Valkauskas, R. (Ekonomika, 2012)
This article is focussed on the problem of economic-statistical calculations and includes an economic-statistical research of economic fluctuations. The author also discusses the rules for statistical identification of economic welfare, economic development features of Lithuania after it became a member of the European Union. The notion of specific economic indicators, their classification issues, and the role and place of economic indicators presenting a systemic view of the country’s economy through identification of economic activities and their development are also discussed. The article deals also with the methodologies based on various statistical methods and offers a methodology for revealing the components of economic fluctuations. A common notion is that the methodologies using analytical time series smoothed with the least squares method for revealing economic fluctuation components are best. The author proposes a methodology for calculating and evaluating the components of economic fluctuations, based on gross domestic product data.